The incidence of vestibular neuritis in Italy - Mandalà, Marco; Salerni, Lorenzo; Ferretti, Fabio; Bindi, Ilaria; Gualtieri, Giacomo; Corallo, Giulia; Viberti, Francesca; Gusinu, Roberto; Fantino, Claudio; Ponzo, Silvia; Astore, Serena; Boccuzzi, Simone; et al. (Frontiers in Neurology, 2023)
Objective: The aim of the study is to estimate the incidence of Vestibular neuritis (VN) in three different districts in Italy, its epidemiological features, and the prevalence of comorbidities associated with it. Methods: An observational prospective study in 198 patients referred to ENT departments in Siena, Grosseto, and Cuneo was carried out over a 2-year period. Each patient underwent a complete otoneurologic examination in the first 48 hours from the onset of symptoms and brain MRI in the early stages of the disease. Follow-up lasted for 1 year. Results: The total VN incidence rate of the three municipalities was 48.497 (95% CI: 48.395–48.598) and its standardized value was 53.564 (95% CI: 53.463–53.666). The total VN incidence rate for the whole sample (municipality and district of the 3 centers) was 18.218 (95% CI: 18.164–18.272) and its standardized value was 20.185 (95% CI: 20.129–20.241). A significant difference was highlighted between patients living in the city compared to those living in the surrounding area (p<), this may be due to the ease of reaching a the otoneurological referral centre. Conclusions: The total incidence rate for the three municipalities was 48.497. This result is higher than previously reported in Literature.